Effectiveness of Using the Cognitive-Pragmatic Method in Primary-Grade Mother Language Education - Zokirov Javohir Gaybullo ugli (Journal of Higher Education and Academic Advancement, 2024)
The article discusses the use of elements of the cognitive-pragmatic method in the process of mother tongue education of the primary grade, the development of students' thinking in mother tongue classes and its directions.